The Role of Microinsurance in Covering Micro Enterprises’ Pure Risks: Case Study of ADIE during 2019–2023 - BOUDRAA , Mohamed Rafik Antar; KRACHE , Houssem (Journal of Excellence for Economics and Management Research, 2024)
The aim of this study is to know how microinsurance contributes in covering micro enterprises’ pure risks. After the presentation of the micro enterprise and the microinsurance, we have studied the case of one of the French associations that cover micro enterprises’ pure risks, which is represented by the ADIE association. Through this study, it has been concluded that microinsurance contributes effectively in covering micro enterprises’ pure risks by the microinsurance products provided often by the microfinance institutions, designed differently with reasonable premiums and few conditions comparing to the traditional insurance products which micro entrepreneurs cannot take.